Respostas metabólicas em girinos de rã- Touro, Lithobates catesbeianus após exposição ao zinco, cobre e cádmio - Chagas, Bianca Roberta Catani (Universidade Federal de São Carlos, 2019)
The metals in the aquatic environment may be incorporated by the local biota and once incorporated may accumulate in organisms and result, even at sublethal level, in biochemical and physiological dysfunctions with important impact on the homeostasis and metabolic performance of these animals. In this context, this study proposes to investigate the activity of lactate dehydrogenase (LDH), malate dehydrogenase (MDH) and glucose, protein and triglyceride levels in the liver, kidney and muscle of bullfrog tadpoles following exposure of 1μg.L-1 of zinc (Zn), copper (Cu) and cadmium (Cd) were isolated and combined for 2 and 16 days. In the exposures to Zn and Cu + Cd the LDH increased in the liver (2 days) and in the kidney decreased in the exposures to Cu and Cd. MDH increased in the liver (Cu + Cd and Zn + Cu + Cd, kidney in all groups combined with metals (16 days) and muscle in the group exposed to Cd (16 days). Glucose levels increased in the liver in the Zn and Cu groups at 2 and 16 days of exposure, and decreased in the kidney (Cu, Cd and Zn + Cu groups) and muscle (Cd) after 2 days of exposure. After 2 days exposure to metals, protein concentrations increased in the liver (Zn) in the kidney in all groups exposed to metals, except in the groups Cd and Zn + Cu + Cd that did not change, and decreased in the muscle in the exposed groups to isolated metals. In relation to the concentration of triglycerides, the kidney and muscle were the most affected, with decrease in the isolated groups and in the Zn + Cu and Zn + Cu + Cd groups at 16 and 2 days of exposure, respectively. There was interaction between the metals in the enzymes and metabolites in the three organs analyzed. Therefore, this study shows that exposure to metals has altered the normal metabolism of animals and that the use of these biomarkers is valid to investigate the damage that exposure to xenobiotics can cause amphibians.
Metabolic responses in tadpoles of bullfrogs, Lithobates catesbeianus after exposure to zinc, copper and cadmium
Keywords: amphibians; biomarkers; glucose; LDH; MDH; Triglycerides; Protein; anfibios; metals; CIENCIAS BIOLOGICAS::BIOQUIMICA